Painting as a Means of Art Therapy for Children – Children with Autism Spectrum Disorder (Case Study in Kaliwungu Kudus State Extraordinary School) - Johan Sutarjo (Jurnal Indonesia Sosial Sains, 2023)
Painting activities can be used as a means of art therapy for children with Autism Spectrum Disorder at the Kaliwungu Kudus State Extraordinary School. The objectives of this study can specifically be formulated: 1). To find out and explain the potential of painting activities for art therapy for children with Autism Spectrum Disorder and 2). To know and explain the implementation of art therapy through painting activities for children with Autism Spectrum Disorder. The benefits of research are generally expected to provide information & input both theoretical and empirical to relevant parties about alternative treatments for the healing process of autistic children through art therapy. In this study, it has used a descriptive study, namely research that has the purpose of describing a situation. This research approach uses qualitative because it examines information, information, & symptoms from a result of the observation process during this study regarding the matter of "Painting as a Means of Art Therapy for Children with Autism Spectrum Disorder (Case Study in The Extraordinary School of Kaliwungu Kudus State)". This research has also been centered on a problem of planning, organizing system, implementation in research, implemented at the Kaliwungu Kudus State Extraordinary School. The research objective focuses on a research problem. The research location is at the Kaliwungu Kudus State Extraordinary School. Research data can be collected with controlled observation techniques, interviews, & documentation. The results of this study show that the type of painting activity that is suitable for children with Autism Spectrum Disorder is painting free expression.